1997
DOI: 10.1104/pp.113.2.327
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Ice Nucleation and Propagation in Plants Using Infrared Video Thermography

Abstract: We evaluated the use of infrared (IR) video thermography to observe directly ice nucleation and propagation i n plants. An imaging radiometer with an HgCdTe long-wave (8-12 pm) detector was utilized to image the thermal response of plants during freezing. IR images were analyzed in real time and recorded on videotape. lnformation on the videotape was subsequently accessed and analyzed utilizing IR image analysis software. Freezing of water droplets as small as 0.5 pL was clearly detectable with the radiometer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
124
0
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 15 publications
(35 reference statements)
7
124
0
4
Order By: Relevance
“…Pseudomonas syringae) can stimulate ice nucleation these have been used in freezing experiments to aid ice formation during infrared observation experiments (Wisniewski et al 1997; Wisniewski 1998; Pearce & Fuller 2001). Typically, plants, which were treated with droplets of INA bacteria began to freeze first compared with samples or plants treated with water droplets only.…”
Section: Utilizing the Infrared Camera In Cold Tolerance In Plantamentioning
confidence: 99%
See 3 more Smart Citations
“…Pseudomonas syringae) can stimulate ice nucleation these have been used in freezing experiments to aid ice formation during infrared observation experiments (Wisniewski et al 1997; Wisniewski 1998; Pearce & Fuller 2001). Typically, plants, which were treated with droplets of INA bacteria began to freeze first compared with samples or plants treated with water droplets only.…”
Section: Utilizing the Infrared Camera In Cold Tolerance In Plantamentioning
confidence: 99%
“…Computer software has also been used to analyze recordings of infrared video tape to study all stages of ice formation and to quantify the magnitude of the exotherms observed and their duration (Al-Swedi et al 2013). Furthermore, the speed of ice front travel can also be determined by determining the start and the end times of the whole tissue being frozen and barriers to ice spread being detected (Wisniewski et al 1997;Pearce & Fuller 2001) (Figure 4).…”
Section: Utilizing the Infrared Camera In Cold Tolerance In Plantamentioning
confidence: 99%
See 2 more Smart Citations
“…An infrared camera and thermal imaging system (Agema Thermovision 800, Agema Infrared Systems, Danderyd, Sweden) were used to produce freezing exotherms (Wisniewski, Lindow & Ashworth 1997) in whole, detached leaves, cooled at 8°C h -1 on 24 October 1996. The cooling chamber consisted of a hollow, cylindrical tower made of styrofoam with internal dimensions of 19·5 × 86·5 cm.…”
Section: Determination Of Freezing Exothermsmentioning
confidence: 99%